The performance of solar PVT cooling through hybrid alumina-silica nanofluids in water - Mohd Radzuan, Nur Hanani; Zakaria, Irnie Azlin; Yahaya, Nor Afifah; Hamzan, Nurlisa; Ramadhan, Anwar Ilmar (UiTM Press, 2025)
The increased demand for efficient renewable solar energy has presented a substantial thermal management challenge for solar photovoltaic thermal (PVT) panels. Since temperature variations majorly affect solar panel efficiency, alternative choices for advanced cooling systems are desperately needed to guarantee better performance. Nanofluids are nanosized particles dispersed in a base fluid that has superior thermal conductivity properties to increase heat transfer performance. This research investigates the effect of an alumina-silica (Al₂O₃:SiO₂) hybrid nanofluid with a volume concentration of 0.5% in water as an alternative coolant in a serpentine channel. The study investigated three various mixing ratios, ranging from 10:90, 50:50, to 30:70 (Al₂O₃:SiO₂) in water with velocity inlet variations (0.0272 – 0.1360 m/s) upon application of 1000 W/m2 heat flux, to mimic the actual implementation of solar PVT. The impact of these hybrid nanofluids on heat transfer performance and pressure drop effect was investigated using computational fluid dynamics (CFD) simulations with Ansys Fluent software. The solar PVT panel temperature was reduced with the adoption of hybrid nanofluids by 0.2% to 0.3% as compared to the base fluid. The heat transfer increment for the 10:90 ratio is 10.2% and 16.9% as the flow rate increases. However, the pressure drop increased in the range of 9.36 Pa to 88.43 Pa and 11.37 Pa to 101.57 Pa for 10:90 and 30:70 respectively as compared to the base fluid. Therefore, hybrid nanofluids feasibility as a cooling fluid for solar PV panel thermal management need to be further reviewed.